The Improvement of Hydroponics Growth Media by Using the Corncob Biochar - Dokmaingam, Pannipha; Kongkratoke, Sitang; Anuwatnonthakate, Amornrat; Yongprapat, Sarayut (Journal of Food Health and Bioenvironmental Science, 2023)
Corncob is one of the main agricultural wastes in the northern part of Thailand. It is utilized in many proposes such as wood pellet, activated carbon or biochar. Biochar has several excellent properties that could provide benefits for agriculture applications such as water absorption, ionic exchange, water holding capacity, and conductivity. These properties could also offer an advantage for the hydroponics system. This study selected corncob biochar for improving the growth of hydroponic plants. Firstly, the commercial biochar will be characterized it’s chemical and physical properties and then hydroponic plants, namely Red Oak lettuces, Green Oak lettuces, and Cos lettuces, were grown in the growth medium with and without biochar in order to compare the growth of plants. It was found that corncob biochar has high aliphatic carbon content with 99.27 % fixed carbon. As the morphology properties, it’s surface area, total pore volume and mean pore diameter are 40.4695 m2/g, 0.0385 cm3/g, 3.85875 nm., respectively. These advantage for promote nutrients utilization in the hydroponics system. These are also affected to different number of leaves of Cos lettuce and dry weight of Green Oak lettuce from growth media with and without biochar which is reached a significant difference level (p<0.05). It was suggested that adding a small amount of corncob biochar could endorse nutrients used in a hydroponics system. This would advantage for put forth shoots of hydroponic plants. However, the biochar would benefit for microbial activity that is important to water and nutrient uptake. This would more advantage if biochar is applied to the soil.